Latin deacon assisting at marriage of two Eastern Catholics: Canon 1108 - Gallaro, George D. (Roman replies and CLSA advisory opinions 1995, 1995)
Can a deacon validly assist/bless at the marriage of two Eastern Catholics subject to a Latin Ordinary?